Cryptomarkets Gamified : What Can We Learn by Playing CryptoKitties? - Serada, Alesja (Digra, 2020)
This paper presents an analysis of CryptoKitties (Axiom Zen 2017) as an educational tool for blockchain adoption. The focus is placed on the official agenda of the game, presented in its white paper (“White Pa-Purr”) and the user guide. I compare statements of the game's developers to the actual practice of playing CryptoKitties for a year. Although gamification of blockchain technologies may have been successful on a broader level of service marketing, the game itself does not make cryptocurrency-based services more accessible to the audience previously unfamiliar with blockchain. However, I conclude that it can launch a longer independent exploration of crypto markets, a potentially transformative experience for the player.
Keywords: blockchain; cryptocurrencies; cryptocurrency studies; crypto games; CryptoKitties; educational games; Ethereum; money games; serious games; fi=Viestintätieteet|en=Communication Studies|